Pengaruh Promosi Dan Pengetahuan Muzakki Terhadap Keputusan Muzakki Membayar Zakat Dengan Religiusitas Sebagai Variabel Mediasi (Studi Kasus Baznas Padang Pariaman) - Yahya, Chaydirul; Rahmat, Rahmat; Candra, Yuni (Jurnal Ilmiah Global Education, 2025)
This study aims to analyze the influence of muzakki promotion and knowledge on muzakki's decision to pay zakat, with religiosity as a mediating variable. The research method used is a quantitative approach with data analysis techniques using Structural Equation Modeling-Partial Least Squares (SEM-PLS) through WarpPLS 8.0 software. Sampling was carried out by purposive sampling by involving a number of muzakki as respondents. The results of the analysis showed that promotion had a positive and significant effect on the decision of muzakki with a contribution of 13% (β = 0.36; p-value = 0.01). Likewise, muzakki knowledge has a positive and significant influence on muzakki decisions with a contribution of 13% (β = 0.23; p-value = 0.01). In addition, promotion also had a significant effect on religiosity with a very large contribution, namely 90% (β = 0.95; p-value = 0.01), while muzakki knowledge contributed 27% to religiosity (β = 0.52; p-value = 0.01). Furthermore, religiosity had a positive effect on the decision of muzakki with a contribution of 10% (β = 0.32; p-value = 0.01). Mediation analysis shows that religiosity is able to mediate the relationship between the promotion and decision of the muzakki, as well as between the knowledge of the muzakki and the decision of the muzakki with a significant indirect effect value. These findings indicate that the strategy of promoting and increasing muzakki knowledge needs to be optimized to increase religiosity and participation of muzakki in giving zakat. The scientific implications of this study confirm that the muzakki decision-making model is not only influenced by rational factors, but also by spiritual aspects. Therefore, this research can be a reference for zakat institutions in designing marketing strategies based on religious values to increase awareness and participation of muzakki in paying zakat